Inhibition of PARP activity does not affect the differentiation processes caused by retinoic acid in SH-SY5Y cells - Horvat, Luka, molekularni biolog (Array, 2019)
Differentiation is a complex process by which cells become specialized in their physiological functions. As this process is followed by a decrease in proliferation ability, the induction of differentiation could be an ideal cancer treatment. We analyzed the effects of a common differentiation agent, retinoic acid, on neuroblastoma SH-SY5Y cells under the conditions of poly(ADP-ribose) polymerase (PARP) inhibition. Namely, PARP1 can be indirectly involved in processes of chromatin remodelling, so the aim was to investigate whether its inhibition can influence the process of differentiation. Cells differentiated after retinoic acid treatment into neural cells, with neurite outgrowth, proliferation arrest and induction of tissue plasminogen activator. PARP inhibition did not influence the process of differentiation. Analysis of gene expression revealed the involvement of several signaling pathways in RA-dependent differentiation. Beside TGFβ and Notch pathways, master transcription factors directing epithelial-mesenchymal transition were shown to also take part in the differentiation process.